Pengabdian Kepada Masyarakat (PKM) Penyuluhan Pemberian Minuman Jahe dan Madu Di Kelurahan Batu Urip RT.01 Kota Lubuklinggau - Sova, Ira Maya; Khasanah, Dwi Uswatun; Sulistiawati, Niken; Ariyani, Putri; Darlina, Yuli; Rossita, Taufianie (Universitas Dehasen Bengkulu, 2024)
Traditional medicine can be used to treat cough in ARI. WHO recommends the use of traditional medicines including herbs in maintaining public health, prevention and treatment of disease, especially for chronic diseases and cancer. Objective: to determine the effect of giving ginger and honey drinks on coughs in toddlers. Method: This type of research is pre-experimental with the research design used is one group pre-test-post test design with a sample of 20 subjects. The instrument used in collecting this data is the respondent'scharacteristic sheet which containsthe name, age, genderalongwiththe observation sheet. Honey ginger therapy intervention was given in the morning and evening for 5 consecutive days with a dose of 1 glass containing 150 ml and 2 teaspoons of pure honey. Result: the results of observations in studies that have been conducted for 5 consecutive days with a frequency of 2x a day obtained a p value of 0.00. Conclusion: There is an Effect of Giving Ginger and Honey Drinks to Ease Coughs in Toddlers.